(3OQGSI aj GdefgLs - (3YHO Gddg(B, (3GHQGgjes ((3HjQhJ(B:s (3GdeQcR GdKbGaj GdYQHj(B,s, 1994)
(3efWb GdHMK aj QDjI GdGehQ hbVGjG efgLjI(B- (3GdeSCdI GdScGfjI hbVjI JfXje GdGSQI(B- (3EYGOI GfJGL GdeSCdI GdScGfjI hJfXje GdGSQI aj GdHdOGf GdYQHjI(B.s
Keywords: (3GdCSQIs; (3GdScGfs; (3JfXje GdCSQIs